Exploring popular information sources and determinants of farmers’ access to agricultural extension services in the Indo-Gangetic plains - Sahu, Subhashree; Bishnoi, Sitaram; Sharma, Ph. Romen; Satyapriya,; Mahra, Girijesh Singh; Burman, Rajarshi Roy; Barua, Sukanya; Misha Madhavan, M.; Sangeetha, V.; Sinha, Sanjeev Kumar; Singh, Rahul; Wason, Monika; et al. (Frontiers in Sustainable Food Systems, 2024)
A study was undertaken to analyse farmers' access to various agricultural extension service sources, their preferences and to delineate underlying determinants for their access. The study used NSSO 77th survey dataset of 14,782 households of IGP states (Bihar, Haryana, Punjab, Uttar Pradesh, West Bengal). Farmers' preferences varied, with private agencies-particularly input dealers-emerging as the top choice, followed by traditional mass media channels and the public extension system. Utility of Cooperative model, and farmer-based organisations have not yet been fully explored for information needs. The inputs (seeds, fertilisers, plant protection) were the most sought-after information. However, in an era of changing needs, farmers should strive to acquire additional information on aspects such as marketing, climate change, and post-harvest functions. The type of information sought by the farmers, influences their preferred sources of extension services. Irrespective of the source, the degree of access diminishes with the decreasing landholding. Among the five IGP states, Haryana emerged as the champion of information access for farmers, while Bihar lagged. Multivariate probit analysis reported that the likelihood of access to agricultural information sources was positively influenced by age, gender, education, size of operational landholding, irrigated area, and sale of produce at MSP. The study suggests making the extension services for small and socio-economically marginalised farmers more inclusive. Inclusiveness of extension services is essential for sustainability because it ensures that all farmers, regardless of their landholding, gender, age, caste, etc., have access to knowledge and resources they need to adopt improved agricultural practices and thus, secure prosperous livelihoods.